THE INFLUENCE OF PERCEIVED HOSPITAL SERVICE QUALITY ON PATIENTS' HEALTH-RELATED QUALITY OF LIFE AND REVISIT INTENTION - Danendra, Albertus Raditya; Irawan, Agustinus Purna; Laksmidewi, Dwinita; Samoedro, Erlang; Eryuniyanti, Eryuniyanti (Graduate Program of Universitas Tarumanagara, 2024)
Improved hospital service quality is anticipated to enhance the Health-Related Quality of Life (HRQL) for patients with heart and internal medicine diseases. This cross-sectional study at Persahabatan General Hospital (RSUP Persahabatan) explores the influence of perceived hospital service quality on HRQL and revisit intentions among 120 cardiology and internal medicine outpatient clinic patients. Findings reveal no direct impact on HRQL and revisit intention, but a significant influence on patient satisfaction and trust. Patient satisfaction acts as a crucial mediator between service quality perception and HRQL and revisit intention, emphasizing the need for enhanced procedural ease and healthcare staff training at RSUP Persahabatan.